Mock elections, electoral participation and political engagement amongst young people in Iceland - Finnbogadóttir, Sara Þöll; Önnudóttir, Eva H. (Stjórnsýslustofnun, 2022)
In this paper, we analyse whether mock elections in Iceland are fulfilling their intended purpose of increasing young voters’ participation in politics and other types of political engagement. Mock elections have been carried out in Icelandic upper secondary schools prior to parliamentary elections since 2016 (and prior to the municipal elections in 2018), but there is no peer-reviewed research about whether these elections are followed by an increase in political participation and engagement amongst young people. Socialisation is a key factor in encouraging political participation amongst young voters as the formative years between childhood and adulthood are a key period in forming behaviour and political attitudes. In this paper, we argue that mock elections have a socialisation impact in terms of increasing young people’s political awareness and engagement, including electoral participation. Based on the results from a survey sent to four upper secondary schools in Iceland, two where mock elections were held and two where they were not held, we found that mock elections have a negligible link to participation in real elections, whether voting made a difference or whether it was considered a civic duty to vote. Other main results are that in schools with mock elections, students were more politically engaged in terms of how interested they were in politics and the frequency which they discussed politics, both of which have been shown to increase the probability of voter turnout.